Hind limb unloading, a model of spaceflight conditions, leads to decreased B lymphopoiesis similar to aging. Issue 2 (5th November 2014) - Lescale, Chloe; Schenten, Veronique; Djeghloul, Dounia; Bennabi, Meriem; Gaignier, Fanny; Vandamme, Katleen; Strazielle, Catherine; Kuzniak, Isabelle; Petite, Herve; Dosquet, Christine; Frippiat, Jean‐Pol; Goodhardt, Michele
ABSTRACT: Within the bone marrow, the endosteal niche plays a crucial role in B‐cell differentiation. Because spaceflight is associated with osteoporosis, we investigated whether changes in bone microstructure induced by a ground‐based model of spaceflight, hind limb unloading (HU), could affect B lymphopoiesis. To this end, we analyzed both bone parameters and the frequency of early hematopoietic precursors and cells of the B lineage after 3, 6, 13, and 21 d of HU. We found that limb disuse leads to a decrease in both bone microstructure and the frequency of B‐cell progenitors in the bone marrow. Although multi‐potent hematopoietic progenitors were not affected by HU, a decrease in B lymphopoiesis was observed as of the common lymphoid progenitor (CLP) stage with a major block at the progenitor B (pro‐B) to precursor B (pre‐B) cell transition (5‐ to 10‐fold decrease). The modifications in B lymphopoiesis were similar to those observed in aged mice and, as with aging, decreased B‐cell generation in HU mice was associated with reduced expression of B‐cell transcription factors, early B‐cell factor (EBF) and Pax5, and an alteration in STAT5‐mediated IL‐7 signaling. These findings demonstrate that mechanical unloading of hind limbs results in a decrease in early B‐cell differentiation resembling age‐related modifications in B lymphopoiesis.—Lescale, C., Schenten, V., Djeghloul, D., Bennabi, M., Gaignier, F., Vandamme, K., Strazielle, C., Kuzniak, I., Petite, H., Dosquet, C., Frippiat, J.‐P., Goodhardt, M. Hind limb unloading, a model of spaceflight conditions, leads to decreased B lymphopoiesis similar to aging. FASEB J . 29, 455‐463 (2015). www.fasebj.org